Cryptanalysis and Improvement of a User Authentication Scheme Preserving Uniqueness and Anonymity for Connected Health Care. - Xu, Lili; Wu, Fan (Journal of Medical Systems, 2015)
Nowadays, connected health care applications are used more and more in the world. Service through the applications can save the patients' time and expense, such as telecare medical information system (TMIS) and integrated electronic patient record (EPR) information system. In the applications, preserving patients' privacy, transmitting messages securely and keeping mutual authentication should all be paid attention. Many authentication schemes have been proposed to make a secure communicating environment. Recently Xie et al. showed that Wen's scheme was insecure because it was under the off-line password guessing attack and without user anonymity and forward security. They gave a new three-factor authentication scheme and claimed that it was secure. However, we find that Xie et al's scheme is vulnerable to the De-synchronization attack and the server has too much storage burden in the scheme. Then we present an improved scheme which overcomes the usual weaknesses and keeps ordinary security characters. Compared with recent schemes of the same kind, our scheme is secure and practical.